2007
DOI: 10.1007/s00535-006-1929-4
|View full text |Cite
|
Sign up to set email alerts
|

Can measurement of chemokines become useful biological and functional markers of early-stage chronic pancreatitis?

Abstract: Chronic pancreatitis, an irreversible inflammatory disease of the pancreas, is characterized by chronic inflammatory cell infiltration, acinar cell degeneration, and development of fibrosis, which lead to impairment of pancreatic exocrine and endocrine function. Despite marked progress in diagnostic tools and, especially, imaging methods, no consensus has been reached on nomenclature in diagnosis of chronic pancreatitis. A major problem is that no reliable diagnostic test exists for early-stage chronic pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…[51][52][53] As a result of increased recruitment of inflammatory cells, activated mononuclear cells release profibrotic cytokines and chemokines, such as TGF-b, TNF-a and MCP-1, which in turn activate hPSCs and promote fibrosis in CP. 4,52,53 The chemokine MCP-1, one of the major monocyte chemoattractants, is highly expressed in fibroblasts in CP, induces TGF-b upregulation and is associated with the progression of pancreatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53] As a result of increased recruitment of inflammatory cells, activated mononuclear cells release profibrotic cytokines and chemokines, such as TGF-b, TNF-a and MCP-1, which in turn activate hPSCs and promote fibrosis in CP. 4,52,53 The chemokine MCP-1, one of the major monocyte chemoattractants, is highly expressed in fibroblasts in CP, induces TGF-b upregulation and is associated with the progression of pancreatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This result supported previous study results and indicated that pancreatic tissue injury and various environmental factors promote CX3CL1 expression in the whole pancreas, so that connection of membrane-bound CX3CL1 and CX3CL1 receptors of inflammatory cells in the pancreatic tissue serves as the basis of the inflammation in CP as it does in chronic hepatitis. 11,17,18,36,37 Furthermore, sheddase is essential for CX3CL1 secretion into the blood. The abundant expression of sheddase in PSCs, as in hepatic stellate cells, 34 indicates that MMP not only enhances extracellular matrix degradation but also induces inflammation by CX3CL1 secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, chemokines and cytokines have been recognized to be important factors in the progression of CP [10,11] . A preliminary study by us in a small number of CP patients showed the possibility that measurement of serum soluble type fractalkine (s-fractalkine) may be useful for diagnosing early-stage of CP [7] . Thus, in the current study, using a large number of CP patients classified by severity with a staging system, we investigated whether chemokine and cytokine levels can become useful biological and functional markers of early-stage CP, focusing particularly on monocyte chemoattractant protein-1 (MCP-1), transforming growth factor beta-1 (TGF-β1), and s-fractalkine, which are supposed to be involved in chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, simple, indirect measurements of decreased pancreatic function do not show abnormality until CP is considerably advanced. Imaging or function tests may not reveal early CP, and the results of these tests do not necessarily correlate with each other [5][6][7][8][9] . The quest continues for useful biological and functional markers of early-stage CP.…”
Section: Introductionmentioning
confidence: 99%